Punitive Attitudes Toward Individuals Convicted of Sex Offenses: A Vignette Study. (19th September 2021) - Socia, Kelly M.; Rydberg, Jason; Dum, Christopher P.
Abstract : The public holds stereotypical beliefs about sex crimes, its perpetrators, and its victims, which may influence punitive attitudes toward individuals convicted of sex offenses (ICSOs). Using a nationally representative vignette survey experiment, we examined whether this punitivity toward ICSOs was influenced by deviations from the stereotypical sex crime case. We also explored whether these influences differed between adult and child victim crimes, and whether they differed between sentencing and post-release supervision policy preferences. We found that the respondents consistently recommended more lenient punishments for female perpetrators and harsher punishments for child victim crimes. A child victim rendered other characteristics less relevant. Despite some similarities between sentencing and post-release policy decisions, male victims elicited longer prison sentences as punishment, while perpetrators with stranger victims yielded more support for post-release policies meant to protect society. Overall, while punitivity toward ICSOs was generally high, the most punitivity was reserved for male perpetrators and child victim crimes.